TINDAKAN PENUNDAAN PENJEPITAN TALI PUSAT BERPENGARUH TERHADAP LAMA KALA III PERSALINAN - Siti Rochmaedah; Natsir Nugroho; Atik Hodikoh (FORIKES, 2018)
Background: At the time of birth, the baby is still attached to the mother through the umbilical cord, which is part of the placenta. Babies would separated from the placenta by clamping and cutting the umbilical cord, and this activity is included in the active management of the third stage of labor, but the optimal time to perform clamping and cutting of the umbilical cord that is controversial and has continued until now. Objective: To determine the effect of delayed umbilical cord clamping of the length of third stage of labor and the amount of bleeding at III-IV stage. Methods: Research with posttest-only control group design. Differential test averages the two groups using independent t-test. Result: There are a different mean of a delayed umbilical cord clamping of the length of third stage of labor p-value 0.04 < 0.05 and there are not significant the amount of bleeding at III-IV stage p-value 0.92 > 0.05. Conclusion & suggestion: Delaying clamping of the umbilical cord effect on the length of third stage of labor and was not effect for the amount of bleeding at III-IV stage. Delayed clamping of the umbilical cord can used as an alternative policy in active management at the third stage of labor. Keywords: Delayed umbilical cord clamping, Length of third stage of labor, Bleeding at III-IV stage